2013
DOI: 10.1136/annrheumdis-2012-203158
|View full text |Cite
|
Sign up to set email alerts
|

EULAR recommendations for the use of imaging of the joints in the clinical management of rheumatoid arthritis

Abstract: Objective To develop evidence-based recommendations on the use of imaging of the joints in the clinical management of rheumatoid arthritis (RA). Methods The task force comprised an expert group of rheumatologists, radiologists, methodologists and experienced rheumatology practitioners from 13 countries. Thirteen key questions on the role of imaging in RA were generated using a process of discussion and consensus. Imaging modalities included were conventional radiography, ultrasound, MRI, CT, dualemission x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
414
2
24

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 553 publications
(446 citation statements)
references
References 116 publications
(108 reference statements)
6
414
2
24
Order By: Relevance
“…Ultrasound (US) and magnetic resonance imaging (MRI) evaluations are more sensitive techniques to identify synovitis than clinical examination and are better than conventional radiography to detect bone erosion (3). The exact position of US in RA management has been recently clarified (4). However, the benefit from these imaging procedures is hampered by their limited availability, which emphasizes the urgent need for widely available soluble biomarkers.…”
Section: Supported By the Espoir (Etude Et Suivi Des Polyarthritesmentioning
confidence: 99%
“…Ultrasound (US) and magnetic resonance imaging (MRI) evaluations are more sensitive techniques to identify synovitis than clinical examination and are better than conventional radiography to detect bone erosion (3). The exact position of US in RA management has been recently clarified (4). However, the benefit from these imaging procedures is hampered by their limited availability, which emphasizes the urgent need for widely available soluble biomarkers.…”
Section: Supported By the Espoir (Etude Et Suivi Des Polyarthritesmentioning
confidence: 99%
“…Current European League Against Rheumatism (EULAR) guidelines for the clinical management of RA are based on MRI and ultrasound scans, but do not include PET or CT scans. 40 While MRI and ultrasound provide outstanding information regarding RA status, these modalities cannot probe the molecular and cellular activity of oedema or synovitis. The strength of PET/CT scans in this area warrants further investigation.…”
Section: Fluorine-18 Fludeoxyglucose Uptake For the First Carpometacamentioning
confidence: 99%
“…Previous studies have demonstrated that ongoing synovitis can be detected by US in up to 62% of patients in clinical remission (19)(20)(21) and that synovitis demonstrated by power Doppler ultrasound (PDUS) correlates with both progression of structural damage (22) and risk of subsequent RA flare (23). As a result, the use of US assessment for patients in clinical remission has been proposed (24).…”
Section: Introductionmentioning
confidence: 99%